2023
DOI: 10.3390/ijms24044217
|View full text |Cite
|
Sign up to set email alerts
|

The “Superoncogene” Myc at the Crossroad between Metabolism and Gene Expression in Glioblastoma Multiforme

Abstract: The concept of the Myc (c-myc, n-myc, l-myc) oncogene as a canonical, DNA-bound transcription factor has consistently changed over the past few years. Indeed, Myc controls gene expression programs at multiple levels: directly binding chromatin and recruiting transcriptional coregulators; modulating the activity of RNA polymerases (RNAPs); and drawing chromatin topology. Therefore, it is evident that Myc deregulation in cancer is a dramatic event. Glioblastoma multiforme (GBM) is the most lethal, still incurabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 330 publications
0
7
0
Order By: Relevance
“…In fact, c-MYC is overexpressed and drives tumorigenesis in more than 40% of human tumors [ 17 ]. Additionally, c-MYC is recognized as a key regulator of stemness and is associated with the regulation of various stem cell properties [ 22 ]. Previous studies have demonstrated the significant role of c-MYC in controlling the self-renewal, survival, and stemness transformation of GSCs [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, c-MYC is overexpressed and drives tumorigenesis in more than 40% of human tumors [ 17 ]. Additionally, c-MYC is recognized as a key regulator of stemness and is associated with the regulation of various stem cell properties [ 22 ]. Previous studies have demonstrated the significant role of c-MYC in controlling the self-renewal, survival, and stemness transformation of GSCs [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the transcriptional level, it is responsible for the upregulation of epidermal growth factor receptor (EGFR). And it participates in the expression or transcriptional inhibition of various microRNAs involved in chemotherapy resistance [ 22 ]. Some of MYC’s oncogenic effects are exerted through its molecular partners within the protein network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the cell cycle, Myc also controls ES metabolism, which mainly depends on aerobic glycolysis [ 89 ], also known as the Warburg effect, a phenomenon extensively investigated in cancer cells [ 90 ]. Myc basically regulates any metabolic pathway, from glycolysis and glutaminolysis to nucleotides, ‘lipids’ and amino acids’ synthesis [ 91 , 92 ]. It has been demonstrated that, upon mir290-mediated derepression, Myc directly binds the promoters of pyruvate kinase M2 ( PKM2) and lactate dehydrogenase A (LDHA) genes, allowing the glycolytic metabolic switch in ES [ 93 ].…”
Section: The Role Of Myc In Pluripotent Stem Cellsmentioning
confidence: 99%
“…MYC is a transcription factor that belongs to the basic helix-loop-helix-leucine zipper (bHLHZip) family and regulates cell growth, differentiation, metabolism, and cell death. Thus, MYC functions as a master regulator of major cellular functions [75][76][77][78]. Studies using knockout mice have shown that MYC is particularly important for cell growth (accumulation of the body mass) and is indispensable during the period of both embryogenesis and adulthood [79].…”
Section: Myc: a Master Regulator Of Cellular Activitymentioning
confidence: 99%